PENINGKATAN KEMAMPUAN MEMBACA PERMULAAN MELALUI PERMAINAN ULAR TANGGADHITA PARANITA NINGTYAS - NINGTYAS, DHITA PARANITA (Program Studi Magister Pendidikan Anak Usia Dini, 2014)
The aim of this research is to improving the beginning reading abilty in group B PAUDPermata Bunda Blitar. The learning process through Ular Tangga consist how to know thealfabet, words, simple sentences and the meaning of words or sentences.The research used actionresearch method according to Kemmis and Taggart made throught two cycle consisting of 16sessions. The cycle consist of planning, action (acting), observation (observing), and reflection(reflecting). Before the beginning observation as a comparison after the action observation isdone, so that the percentage target of the learning achievement could be measured. With Ulartangga game, its prove if learn reading can with games and it is can make easy learn reading. Thedata was collected by the research instrument in the form of the test result to early reading abilitypre-cycle and the results to early reading ability after cycle I and cycle II. The end result of thisresearch shows that the reading throught Ular Tangga game could increase early reading abilityof grade B Kindergarten student who evidenced by the acquisition of clasical scores early readingpre-action reaches 38,88%. After the first cycle increase the scores reaches 79,67% and thesecond cycle is optaineded satisfactory clasical scores reaches 90%. Ular tangga game it shouldbe alternatif to teach reading for the children. Keywords: Reading Ability, Early Childhod, Ular Tangga Game Abstrak: Tujuan penelitian untuk meningkatkan kemampuan membaca permulaan anak TK BdiPAUD Permata Bunda Blitar. Kemampuan membaca permulaan meliputi kemampuan untukmengenal huruf, suku kata, kata, membaca kalimat dan memaknai kata dan kalimat. Penelitian inimenggunakan metode penelitian tindakan menurut Kemmis dan Taggart dengan dua siklus yangterdiri dari 16 pertemuan. Siklus terdiri dari perencanaan (planning), tindakan (acting),pengamatan (observasi), dan mencerminkan (refleksi). Penelitian pra tindakan untuk mengetahuihasil presentase kemampuan awal. Dengan permainan ular tangga, dapat membuat belajarmembaca menjadi lebih mudah. Hasil penelitian menjelaskan bahwa kemampuan membaca anakkelompok B meningkat, yang dilihat dari kenaikan skor klasikal dari kegiatan pra tindakan38,88%. Setelah diadakan siklus I menjadi meningkat 79,67%, dan siklus II meningkat menjadi90%. Permainan ular tangga dapat mejadi alternatif mengajarkan membaca untuk anak. Kata kunci: Kemampuan Membaca, Anak Usia Dini, Permainan Ular Tangga